Social identity and mobility in Trikeri - Beopoulou, Ioanna (The Greek Review of Social Research, 1981)
Trikeri is an isolated Pélion village with marked insular characteristics. At the end of the 18th century and the beginning of the 19th, it took an active part in the development of the Greek mer chant marine and became one of the important maritime centers in the area. Because of its maritime activities, economic and social structures are based upon the men’s departure and the women’s permanent presence in the village community. The institutions of endogamy, of uxorilocality and of property transmission as well as women’s control over the household economy and the matrimonial alliances express thisstate of separation between the sexes. Living in a spatial and tern poral discontinuity along with the post-marital residence pattern, the men are mobile also within their own society. Furthermore, village membership rests upon relations through women who are responsible for the group’s cohesion. Most of these structures have been maintained up to now. Economic activities still depend on the sea but the social hierarchy has been altered. The wealthy class which emerged in the times of economic development has been disaggregated. Today, the men’s massive enrollment in the merchant marine results in social uniformi tyTrikeri remains, as it did in the past, a society whose monetary economy, dependent on a wider market, guarantees a high standard of living to the villagers. The presence of money allows the in habitants to cope with the pressures of modern times. Numerous oh jects, signs of modernity, are now being integrated into yesterday’s codes of prestige symbols. Nevertheless, the impact of the images from the outside world conveyed by the mass-media is increasing. Sailors are no longer ideal husbands in the eyes of the young women, a fact which generates a tendency towards exogamy. At the same time, a few families have moved to Volos in order to help their sons to go through technical schools and a road is being built which leads to the other Pelion villages breaking Trikeri’s isolation. These changes make Trikeri more and more open to the external world and lead to a social destabilization.